Milia En Plaque as a Distinct Follicular Hamartoma With Cystic Trichoepitheliomatous Features. (March 2016) - Terui, Hitoshi; Hashimoto, Akira; Yamasaki, Kenshi; Aiba, Setsuya
Abstract : Abstract: Milia en plaque (MEP) is an uncommon disorder characterized by an erythematous plaque containing numerous milia. The pathogenesis of MEP is not clear. The authors report a man with an erythematous plaque on the right retroauricular area, containing numerous white-yellow cysts varying in size. Histological examination showed that multiple cystic structures at various levels of the dermis that were lined by stratified squamous epithelium and contained keratinous material—these findings were consistent with the diagnosis of multiple milia. In addition to epidermal cysts, however, the lesion consisted of a branched proliferation of pale-staining keratinocytes lined with basal keratinocytes budding from the overlying epidermis. Moreover, some cysts were formed within the branched epithelial proliferation, had thicker cyst walls than the ordinary milium, or had irregular or branched projections toward the surrounding dermis. From these findings, the authors conclude that MEP is a distinct follicular hamartoma with cystic trichoepitheliomatous features.